Developing Community Based Rehabilitation to Build A Low-cost and Wide-coverage Health Care Service System - Lidian CHEN (康复学报)
To develop rehabilitation service is a necessary requirement for embracing the challenge of growing demands from chronic diseases and aging population. At this stage, rehabilitation medicine remains vulnerable and lack of accessibility. To develop community based rehabilitation and to build a high-quality, low-cost and widecoverage health care service system can not only improve people's heath, but also provide'Chinese solution'to the global health.